Dual additive polishing composition for glass substrates

The CMP compositions, featuring pyrophosphate and sulfonate or quaternary ammonium compounds, address the challenge of balancing high removal rates with surface finish quality, achieving enhanced polishing efficiency and quality on glass substrates.

JP2025510186APending Publication Date: 2025-04-14CMC MATERIALS INC
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
JP2024556552
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2022-03-24
Filing Date
2023-02-16
Publication Date
2025-04-14

AI Technical Summary

Technical Problem

The demand for improved chemical mechanical polishing (CMP) compositions to enhance throughput and storage density on glass substrates used in hard disk drives has not been met, as existing compositions struggle to balance high material removal rates with surface finish quality.

Method used

The development of CMP compositions comprising a liquid carrier, abrasive particles, pyrophosphate compounds, and either sulfonate anionic surfactants or quaternary ammonium compounds, which work synergistically to increase removal rates while maintaining or improving surface finishes.

Benefits of technology

The proposed CMP compositions achieve higher removal rates and improved surface finishes on glass substrates, demonstrating synergistic effects that enhance polishing efficiency and quality beyond the capabilities of individual components.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025510186000001
    Figure 2025510186000001
  • Figure 2025510186000002
    Figure 2025510186000002
  • Figure 2025510186000003
    Figure 2025510186000003
Patent Text Reader

Abstract

A chemical-mechanical polishing composition comprising, consisting of, or consisting essentially of a liquid carrier, abrasive particles in the liquid carrier, a pyrophosphate compound, and a sulfonate compound or a compound containing a quaternary ammonium group.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] FIELD OF THE DISCLOSURE Embodiments disclosed herein relate to chemical mechanical polishing compositions for polishing glass substrates, and more particularly, to compositions that include a pyrophosphate compound and a sulfonate compound or a quaternary amine. [Background technology]

[0002] The hard disk drive industry continues to demand increased storage capacity and smaller size, which creates a corresponding demand for smaller memory or rigid disks with greater storage (or data) density, and requires improved processes for polishing such memory or rigid disks.

[0003] As used herein, the term "memory or rigid disk" refers to any magnetic disk, hard disk, rigid disk, or memory disk used to hold information in electromagnetic form. These memory or rigid disks, referred to herein simply as disks or substrates, are generally of one of two types: (i) Nickel-phosphorus plated aluminium discs; or (ii) Glass disk. During manufacturing, these disks are polished to exacting surface finish tolerances and then deposited with the magnetic material that will ultimately be used for data storage.

[0004] As is well known, the data storage industry is subject to continuous, and sometimes extreme, price pressures. To maintain an economically favorable process, high throughput is generally required, which in turn dictates high material removal rates during polishing operations. However, increasing removal rates also increases surface roughness or surface waviness.

[0005] While chemical mechanical polishing (CMP) compositions and methods for polishing nickel phosphorus and / or glass disks are commercially available, there is an unmet need for improved polishing compositions to improve throughput and enable increased storage densities, particularly polishing compositions that provide improvements in surface finish (e.g., reduced surface roughness and waviness) and higher material removal rates.

[0006] Summary of the Invention A chemical mechanical polishing composition is disclosed that contains, consists of, or consists essentially of a liquid carrier, abrasive particles within the liquid carrier, a pyrophosphate compound, and a sulfonate anionic surfactant or a sulfonate compound, including a polysulfonic acid.

[0007] In another embodiment, the disclosed polishing composition comprises, consists of, or consists essentially of a liquid carrier; abrasive particles within the liquid carrier; a pyrophosphate compound; and a cationic compound comprising a quaternary ammonium cation.

[0008] Detailed Description of the Invention A chemical mechanical polishing composition is disclosed. The composition contains, consists of, or consists essentially of a liquid carrier, abrasive particles in the liquid carrier, a pyrophosphate compound, and a sulfonate anionic surfactant, or an anionic polymer containing sulfonic acid groups, or a compound containing quaternary ammonium groups. In certain embodiments, the composition contains, consists of, or consists essentially of a liquid carrier, abrasive particles in the liquid carrier, and a synergistic combination of a pyrophosphate compound and a sulfonate anionic surfactant, or an anionic polymer containing sulfonic acid groups, or a synergistic combination of a pyrophosphate compound and a compound containing quaternary ammonium groups.

[0009] While the disclosed embodiments are not limited in this respect, the disclosed compositions can be advantageously used to polish glass substrates (such as those used in the construction of memory or rigid disks in hard disk drives).As will be described in more detail below by way of example, the disclosed polishing compositions include a synergistic combination of chemical additives, which has been found to advantageously significantly improve polishing rates.Certain of the disclosed embodiments have also been found to provide comparable or even improved surface finishes (e.g., surface waviness).

[0010] It will be understood that the term "synergistic" (or synergistic effect) is used according to the definition of the term in standard dictionaries. Synergistic effect is defined as the interaction of multiple elements whose combined effect is greater than the sum of their individual effects (Dictionary of Science and Technology, Academic Press, 1992). In the disclosed embodiments, it has been found that the combination of a pyrophosphate compound with a sulfonate compound (e.g., a disulfonate anionic surfactant) or with a quaternary ammonium compound increases the removal rate in polishing a glass substrate by more than the sum of the individual contributions of the pyrophosphate compound and the sulfonate compound. Furthermore, as will be described in detail in the following examples, it has been found that the addition of a sulfonate compound or a quaternary ammonium compound to a composition containing a pyrophosphate compound unexpectedly increases the removal rate (as opposed to the expected decrease in the removal rate).

[0011] The disclosed polishing compositions generally contain abrasive particles dispersed or suspended in a liquid carrier. The liquid carrier is used to facilitate application of the abrasive particles and chemical additives to the surface of the substrate to be polished. The liquid carrier can include any suitable carrier (e.g., solvent), which may include lower alcohols (e.g., methanol, ethanol, etc.), ethers (e.g., dioxane, tetrahydrofuran, etc.), water, and mixtures thereof. The liquid carrier preferably consists of, or consists essentially of, deionized water.

[0012] The disclosed polishing compositions may include abrasive particles in a liquid carrier (e.g., dispersed or suspended in a liquid carrier). The abrasive particles may include virtually any abrasive particles suitable for polishing glass substrates, such as metal oxide particles, diamond particles, and / or ceramic particles. The metal oxide particles may include, for example, silica, ceria, and / or alumina abrasive particles (including colloidal and / or fumed metal oxide particles). The ceramic particles may include materials such as cubic boron nitride or silicon carbide.

[0013] Preferred embodiments include silica abrasive particles, such as fumed or colloidal silica abrasive particles. As used herein, the term colloidal silica particles refers to silica particles produced by a wet process. Colloidal silica may be precipitated silica or condensation-polymerized silica, which can be produced by methods known to those skilled in the art, such as by sol-gel or silicate ion exchange. Condensation-polymerized silica particles are often produced by condensing Si(OH)4 to form substantially spherical particles. Fumed silica is obtained by pyrogenic or flame hydrolysis processes (reacting silicon tetrachloride with oxygen in a flame) and generally has an aggregate structure, where roughly spherical primary particles are fused together to form chain-like aggregates.

[0014] The abrasive particles (e.g., colloidal silica particles) can have virtually any suitable particle size. The particle size of the particles suspended in the liquid carrier can be determined by various means in the industry. For example, the particle size can be determined as the diameter of the smallest sphere that encircles the particle and can be measured by various commercially available instruments, including, for example, the CPS Disc Centrifuge, Model DC24000HR (CPS Instruments, Prairieville, Louisiana, USA), or the Zetasizer® from Malvern Instruments®. The abrasive particles can have an average particle size of about 5 nm or more (e.g., about 10 nm or more, about 15 nm or more, or about 20 nm or more). The abrasive particles can have an average particle size of about 100 nm or less (e.g., about 50 nm or less, about 45 nm or less, or about 40 nm or less). Thus, the colloidal silica particles can have an average particle size in the range of about 5 nm to about 50 nm (e.g., about 10 nm to about 40 nm, about 15 nm to about 40 nm, or about 20 nm to about 40 nm). For example, in one advantageous embodiment, the abrasive particles comprise colloidal silica having an average particle size of about 30 nm.

[0015] The polishing composition may include any suitable amount of the above-mentioned abrasive particles. For example, the abrasive particles may include about 1 wt% or more (e.g., about 2 wt% or more, about 3 wt% or more, or about 5 wt% or more) of the abrasive particles when used. The amount of the abrasive particles in the polishing composition may include about 20 wt% or less (e.g., about 15 wt% or less, about 12 wt% or less, or about 10 wt% or less) when used. It is understood that the amount of the abrasive particles may be in a range bounded by any two of the above endpoints, such as about 1 wt% to about 20 wt% when used (e.g., about 2 wt% to about 20 wt%, about 5 wt% to about 15 wt%, about 5 wt% to about 12 wt%, or about 5 wt% to about 10 wt%). For example, in one advantageous embodiment, the polishing composition may include about 8.5 wt% of colloidal silica when used.

[0016] The polishing composition disclosed further comprises a pyrophosphate compound. As used herein, the term pyrophosphate compound refers to a compound that comprises a phosphorus oxyanion with two phosphorus atoms in the POP bond. It will be understood that pyrophosphate compounds are generally referred to in the chemical arts as diphosphates, or diphosphate compounds (presumably because the phosphorus oxyanion comprises two phosphorus atoms). The disclosed embodiments can comprise substantially any suitable pyrophosphate compound, including, for example, disodium pyrophosphate (DSPP), tetrasodium pyrophosphate (TSPP), dipotassium pyrophosphate (DKPP), and tetrapotassium pyrophosphate (TKPP). Preferred pyrophosphate compounds include TSPP and TKPP.

[0017] The polishing composition may contain the pyrophosphate compound in substantially any suitable amount. For example, the polishing composition may contain about 0.001 wt% (10 wtppm) or more (e.g., about 0.01 wt% or more, or about 0.02 wt% or more) of the pyrophosphate compound when used. The amount of the pyrophosphate compound in the polishing composition may be about 1 wt% or less (e.g., about 0.5 wt% or less, about 0.3 wt% or less, or about 0.2 wt% or less) when used. It is therefore understood that the amount of the pyrophosphate compound may be in a range bounded by any two of the above endpoints, for example, in a range of about 0.001 wt% to about 1 wt% when used (e.g., about 0.01 wt% to about 0.5 wt%, about 0.01 wt% to about 0.3 wt%, about 0.02 wt% to about 0.3 wt%, or about 0.02 wt% to about 0.2 wt%). For example, in certain advantageous embodiments, the polishing composition, when used, can contain about 0.03 wt. %, 0.06 wt. %, 0.08 wt. %, or about 0.12 wt. % TKPP.

[0018] The disclosed polishing composition may further comprise a second additive compound (in addition to the pyrophosphate compound). The second additive compound may comprise either (i) a sulfonate compound containing a sulfonate anionic surfactant, or an anionic polymer containing a sulfonic acid group, or (ii) a compound containing a quaternary ammonium group (also referred to herein as a quaternary amine or quaternary ammonium compound). As will be described in more detail in the following examples, the combination of the pyrophosphate compound and the second additive compound may advantageously be a synergistic combination that significantly increases the removal rate during polishing while also improving the surface finish of the polished substrate.

[0019] In certain embodiments, the second additive compound can comprise virtually any suitable anionic surfactant or anionic polymer (polysulfonic acid) that comprises sulfonic acid groups.For example, the sub-category of suitable sulfonate anionic surfactants can include alkylarylsulfonates (e.g., alkylbenzenesulfonates, e.g., dodecylbenzenesulfonates), alkylsulfonates (e.g., alkenylsulfonates, e.g., α-olefinsulfonates, alkylglyceridesulfonates, alkylethersulfonates, and alkylsulfoacetates), alkyldiphenyloxidesulfonates, sulfosuccinates (e.g., monoalkylsulfosuccinates, and dialkylsulfosuccinates), acyltaurates, and acylisethionates.

[0020] In certain preferred embodiments, the sulfonate anionic surfactant comprises a disulfonate anionic surfactant, including, for example, an alkyldiphenyloxide disulfonate anionic surfactant having the following structure: TIFF2025510186000001.tif31170

[0021] In the formula, R is C1 to C 30 , preferably C6 to C 30 , more preferably C6 to C 22wherein the alkyl group optionally contains one or more heteroatoms selected from the group consisting of O and N; X + is H or a cation, such as an alkali metal cation or an alkaline earth metal cation (e.g., sodium, potassium, lithium, calcium, magnesium, etc.). Examples of suitable alkyldiphenyloxide disulfonate surfactants include those commercially available from Dow Chemical Company, Midland, Mich., under the trade designations Dowfax® 2A1, Dowfax® 3B2, Dowfax® 8390, Dowfax® C6L, Dowfax® C10L, and Dowfax® 30599.

[0022] Non-limiting examples of polymers or copolymers containing sulfonic acid groups include polystyrene sulfonic acid, polyvinyl sulfonic acid (PVSA), poly(2-acrylamido-2-methylpropanesulfonic acid), poly(styrenesulfonic acid-co-maleic acid), and poly(acrylic acid)-co-poly(2-acrylamido-2-methylpropanesulfonic acid).

[0023] In the embodiment that comprises sulfonate anionic surfactant or polysulfonic acid, the composition can comprise the second additive compound in substantially any suitable amount.For example, the polishing composition can comprise about 0.001 wt% (10 wtppm) or more (e.g., about 0.01 wt% or more, or about 0.02 wt% or more) of the second additive compound when used.The amount of the second additive compound in the polishing composition can be about 1 wt% or less (e.g., about 0.5 wt% or less, about 0.3 wt% or less, or about 0.2 wt% or less) when used. Thus, it is understood that the amount of the second additive compound can be in a range bounded by any two of the above endpoints, such as, for example, about 0.001% to about 1% by weight when used (e.g., about 0.01% to about 0.5% by weight, about 0.01% to about 0.3% by weight, about 0.02% to about 0.3% by weight, or about 0.02% to about 0.2% by weight). For example, in certain advantageous embodiments, the polishing composition can include about 0.05% by weight of Dowfax® 2A1, Dowfax® 3B2, Dowfax® C6L, or Dowfax® C10L when used.

[0024] The disclosed embodiments comprising a sulfonate anionic surfactant or polysulfonic acid further optionally comprise an anionic (or another anionic) polymer, including, for example, poly(acrylic acid) (PAA), poly(methacrylic acid) (PMAA), poly(maleic acid) (PMA), and the like. The use of such polymers in the polishing composition can advantageously control friction during the polishing operation and reduce waviness of the substrate. Such polymers do not synergistically interact with the pyrophosphate compound and / or the sulfonate compound. Exemplary compositions can comprise from about 0 to about 1000 ppm by weight of such optional anionic polymers (e.g., from about 30 to about 300 ppm by weight of PAA or PMAA in certain embodiments).

[0025] The term "sulfonate" as used herein is understood to refer to the ionized (anionic) form of the surfactant (or polymer) (containing at least one anionic oxygen) and also to the acid form of the surfactant (containing at least one acid OH group). As is well known in the chemical arts, the acid forms of many sulfur-based surfactants are generally highly acidic and tend to become ionized even at relatively low pH values ​​(e.g., pH 2-3). Thus, the anionic surfactants in the CMP compositions of the present invention may generally exist primarily in the anionic form, regardless of whether the surfactant is added to the composition in the form of a salt or in the form of an acid.

[0026] In certain other embodiments, the second additive compound can include substantially any suitable quaternary amine (i.e., substantially any suitable compound that includes a quaternary ammonium group). Such compounds can be represented by the following chemical formula: --N + R'R' 'R' ' ' In the formula, R', R'' and R'' may be the same or different and may include virtually any carbon-containing compound. It is understood that the n-ium group in the quaternary ammonium may have a structure corresponding to that of the tertiary amine as the raw material. For example, if the tertiary amine is triethylamine, the corresponding quaternary ammonium group is triethylammonium. The quaternary ammonium group may be, for example, one having a saturated hydrocarbon group (e.g., trimethylamine, triethylamine, dimethylethylamine, etc.), one having a hydroxyl group, an ether group, an amino group, and / or one having a hydrocarbon group with an unsaturated carbon bond (e.g., dimethylethanolamine, dimethylaniline, diethylaniline, dimethylbenzylamine, pyridine, etc.).

[0027] In a preferred embodiment, the compound containing a quaternary ammonium group comprises a tetramethylammonium group, a tetraethylammonium group, a tetrabutylammonium group, a benzyltributylammonium group, or a mixture thereof. In a most preferred embodiment, the compound comprises tetraethylammonium hydroxide.

[0028] In embodiments that include a compound having a quaternary ammonium group, the composition may include the compound in substantially any suitable amount. For example, the polishing composition may include about 0.001 wt. % (10 ppm) or more (e.g., about 0.01 wt. % or more, or about 0.02 wt. % or more) of the compound when used. The amount of the compound in the polishing composition may be about 0.5 wt. % or less (e.g., about 0.4 wt. % or less, about 0.3 wt. % or less, or about 0.2 wt. % or less) when used. It is understood that the amount of the compound may be in a range bounded by any two of the above endpoints, for example, about 0.001 wt. % to about 0.5 wt. % (e.g., about 0.01 wt. % to about 0.5 wt. %, about 0.01 wt. % to about 0.4 wt. %, about 0.002 wt. % to about 0.3 wt. %, or about 0.002 wt. % to about 0.2 wt. %) when used. For example, in certain advantageous embodiments, the polishing composition, when used, can contain about 0.02 wt %, 0.05 wt %, 0.1 wt %, or 0.2 wt % tetraethylammonium hydroxide.

[0029] The disclosed polishing compositions are generally acidic, with a pH of less than about 7. The pH is, for example, greater than about 1 (e.g., greater than about 1.5). The pH can be less than about 5 (e.g., less than about 4, less than about 3.5, or less than about 3). It is understood that the pH of the polishing composition can be in a range bounded by any two of the above endpoints, for example, in the range of about 1 to about 5 (e.g., about 1 to about 4, about 1.5 to about 3, or about 1.5 to about 3). For polishing compositions containing a pyrophosphate compound and a sulfonate compound, the pH can preferably be in the range of about 1.5 to about 2. For polishing compositions containing a pyrophosphate compound and a quaternary amine, the pH can most preferably be in the range of about 2 to about 3.

[0030] The pH of the polishing composition can be achieved and / or maintained by any suitable means. The polishing composition can include virtually any suitable pH adjuster or buffer system known to those skilled in the chemical arts. For example, suitable pH adjusters can include various acids, including nitric acid, sulfuric acid, phosphoric acid, and the like.

[0031] The disclosed polishing compositions can include virtually any additional, optional chemical additive. For example, the disclosed compositions can further include one or more dispersants and / or biocides. Such additional additives are purely optional. The disclosed embodiments are not so limited and do not require the use of one or more of such additives. In further embodiments that include a biocide, the biocide can include any suitable biocide.

[0032] The polishing composition can be produced using any suitable technique, many of which are known to those skilled in the art. The polishing composition can be produced in a batch process or a continuous process. In general, the polishing composition can be produced by combining the components of the composition in any order. As used herein, the term "component" includes each component (e.g., colloidal silica, pyrophosphate, and second additive compound).

[0033] For example, the components of the polishing composition can be added directly to a dispersion containing the abrasive particles. Alternatively, the abrasive can be added to a solution containing the pyrophosphate and the second additive compound. In either case, the abrasive particles and other components can be blended together by any technique suitable to achieve adequate mixing. Such blending / mixing techniques are well known to those skilled in the art.

[0034] The polishing composition of the present invention may also be provided as a concentrate intended to be diluted with an appropriate amount of water before use. In such an embodiment, the polishing composition concentrate may include an abrasive (e.g., silica), a pyrophosphate compound, a second additive compound, and any other optional compounds such that, upon dilution of the concentrate with an appropriate amount of water, each component of the polishing composition is present in the polishing composition in an amount within the appropriate ranges described above for each component. For example, colloidal silica and each of the other optional components may be present in the polishing composition in an amount that is about 2 times (e.g., about 3 times, about 4 times, or about 5 times) greater than the use concentration described above for each component. This results in each component being present in the polishing composition in an amount within the ranges defined above for each component when the concentrate is diluted with an equal volume (e.g., 1 volume of water, 2 volumes of water, 3 volumes of water, or 4 volumes of water). Furthermore, as will be understood by those skilled in the art, the concentrate may include an appropriate fraction of the water present in the final polishing composition to ensure that the other components are at least partially or completely dissolved in the concentrate.

[0035] The disclosed compositions may be advantageously used to polish glass substrates, preferably rigid disk glass substrates. The disclosed compositions may be used in conjunction with a suitable polishing machine for polishing glass substrates (e.g., rigid disk glass substrates). Such polishers typically include upper and lower platens and are configured to polish multiple substrates simultaneously on both sides. Each platen has a polishing pad attached thereto, and the platens are typically rotated independently and in opposite directions.

[0036] During the polishing operation, the substrate is loaded with one or more carriers that engage with internal and external gears on the lower platen. The rotational speed of the carriers is controlled by controlling the rotation of the gears. The upper platen is lowered into contact with the substrate, and the polishing composition is distributed through the upper platen (and upper pad) to the substrate. The rotational speeds of the platens and carriers are selected so that the top and bottom sides of the substrate are polished at approximately the same speed.

[0037] The effectiveness of the polishing process can be characterized in many ways, for example in terms of polishing removal rate and in terms of surface roughness or surface waviness of the polished substrate. The removal rate can be determined, for example, by measuring mass loss (weighing the substrate before and after polishing) and determining the amount of substrate removed per unit time of polishing. Surface roughness can be evaluated in terms of average roughness (Ra) or surface waviness (HMS_Wq), for example, by profiler or atomic force microscope (AFM) measurement, or by optical measurement techniques, for example, using KLA Tencor's Candela 6100 or 6300 equipment.

[0038] The substrate can be polished with the disclosed composition using any suitable polishing pad. Suitable pads include, for example, woven or non-woven polishing pads. Furthermore, suitable polishing pads can include any suitable polymer with a variety of density, hardness, thickness, compressibility, ability to bounce back when compressed, and compression modulus. Suitable polymers include, for example, polyvinyl chloride, polyvinyl fluoride, nylon, fluorocarbon, polycarbonate, polyester, polyacrylate, polyether, polyethylene, polyamide, polyurethane, polystyrene, polypropylene, products formed therewith, and mixtures thereof.

[0039] It will be understood that the present disclosure includes many embodiments, including but not limited to the embodiments recited in the claims.

[0040] The present invention is further illustrated by the following examples which, of course, should not be construed as in any way limiting its scope.

[0041] Example 1 This example illustrates the synergistic combination of a pyrophosphate compound and a sulfonate anionic surfactant in the disclosed polishing compositions. Each polishing composition contains 8.5 wt. % colloidal silica having an average particle size of 30 nm and sufficient nitric acid to adjust the pH to 1.8. Polishing Composition 1A contains no other ingredients. Polishing Compositions 1B-1I further contain tetrapotassium pyrophosphate (TKPP) and / or an alkyldiphenyloxide disulfonate anionic surfactant (DOWFAX® C10L) in the amounts shown in Table 1 (all amounts in weight percent).

[0042] Each composition was used to polish six separate glass disks (substrates) (six disks were polished simultaneously in each trial). The trials were performed using a Hamai 9B double-sided polishing tool with a lower platen speed of 60 rpm, carrier rotation speed of 20 rpm, carrier rotation of 12 rpm, and a downforce of 33 g / m. 2 and slurry flow rate of 600 ml / min for 11 minutes. The polishing rate was determined based on mass loss, and surface waviness (HMS_Wq) was determined for two of the six disks using a measuring tool Candela 6100. The results of removal rate and surface waviness are listed in Table 1. These results are normalized to the removal rate and surface waviness achieved using polishing composition 1A. TIFF2025510186000002.tif129170

[0043] As shown in Table 1, the addition of disulfonate surfactants (1B and 1C) to the base composition (1A) improved waviness at the expense of a decreased removal rate (waviness decreased to normalized values ​​of 76 and 66 at the expense of a decreased removal rate of normalized values ​​of 85 and 73). An increase in removal rate was observed by adding pyrophosphates (1D, 1E, 1F, 1G, and 1H) to the base composition (1A), even at the expense of increased waviness (with increasing TKPP concentration, removal rates increased to normalized values ​​of 115, 130, 138, 152, and 151 at the expense of increased waviness to normalized values ​​of 110, 115, 115, 120, and 121).

[0044] An unexpected synergistic interaction was observed for composition 1I, where the addition of a disulfonate surfactant to a composition containing a pyrophosphate compound significantly improved both removal rate and surface waviness. Comparing the results for composition 1I with 1F, the addition of the disulfonate surfactant increased the removal rate from 138 to 155 normalized values ​​and reduced waviness from 115 to 107 normalized values. Any further improvement in removal rate was not expected (since a decrease in removal rate was observed with the addition of the disulfonate surfactant for compositions 1B and 1C) and was synergistic. If the combination of pyrophosphate and disulfonate anionic surfactant were assumed to be merely additive (or less), a maximum removal rate of 111 would be predicted for composition 1I (an increase of 38 and a decrease of 27, for a net increase of 11). Thus, the observed removal rate of 155 is clear evidence of a synergistic effect.

[0045] Example 2 This example further illustrates the synergistic combination of a pyrophosphate compound and an anionic sulfonate surfactant in the disclosed polishing composition, and the effect of an optional anionic polymer additive. Each polishing composition contained 8.5 wt. % colloidal silica, with an average particle size of 30 nm, and sufficient nitric acid to adjust the pH to 1.8. Polishing Compositions 1C, 1G, and 1I were as described above in Example 1. Polishing Compositions 2A-2G further contained TKPP and / or DOWFAX® C10L in the amounts shown in Table 2 (all amounts in weight percent). Compositions 2A-2G further contained 0.01 wt. % (100 wt. ppm) of polyacrylic acid having a molecular weight of 250,000 g / mol.

[0046] Six separate glass disks (substrates) were polished with each composition using a Hamai 9B double-sided polishing tool under the polishing conditions previously described in Example 1. The polishing rate and surface waviness HMS_Wq were also determined as previously described in Example 1. The removal rate and surface waviness results are shown in Table 2. These results are normalized to the removal rate and surface waviness achieved using Polishing Composition 1A as reported in Table 1. TIFF2025510186000003.tif148170

[0047] As shown in Table 2, the addition of PAA was observed to reduce surface waviness and removal rate. In the absence of TKPP, the addition of PAA to compositions containing disulfonate surfactants (comparison of compositions 2A-1C) reduced the removal rate to a normalized value of 73-72 and reduced the waviness to a normalized value of 66-60. PAA did not participate in or interfere with the synergistic effect with the pyrophosphate compound and the disulfonate surfactant. In compositions containing a synergistic combination of TKPP and disulfonate surfactants, the addition of PAA (comparison of compositions 2B and 1I) reduced the removal rate to a normalized value of 155-154 and reduced the waviness to a normalized value of 107-102.

[0048] The synergistic interaction between the pyrophosphate compound and the disulfonate surfactant was further observed in compositions 2C-2G, where the addition of the disulfonate surfactant to the TKPP-containing composition significantly improved both the removal rate and waviness. Comparing compositions 2C-2F with composition 1G, it was observed that the removal rate increased from a normalized value of 152 to normalized values ​​of 156, 163, 174, and 185, and the waviness decreased from a normalized value of 120 to normalized values ​​of 117, 109, 106, and 102 with increasing concentration of the disulfonate surfactant.

[0049] Example 3 This example shows that the synergistic interaction was not observed for the polishing compositions containing other phosphate compounds (in other words, the synergistic interaction was observed only for the compositions containing pyrophosphate compounds).As described for Example 1, each composition contains 8.5 wt.% colloidal silica, with an average particle size of 30 nm, and sufficient nitric acid to adjust the pH to 1.8.Polishing Compositions 1G and 2E are as described above for Examples 1 and 2. Polishing Compositions 3A and 3B further included 0.093 wt% hydroxyethylidene diphosphinic acid (HEDP), Compositions 3C and 3D further included 0.259 wt% diethylenetriaminepenta(methylenephosphonic acid) (DTPMPA), Compositions 3E and 3F further included 0.122 wt% 2-phosphonobutane 1,2,4-tricarboxylic acid (PBTC), and Polishing Compositions 3G and 3H further included 0.5 wt% tartaric acid (carboxylic acid). Note that the molar concentration of the phosphate or carboxylic acid additive was the same for Compositions 1G, 2E, and 3A-3H. Compositions 1G, 3B, 3D, 3F, and 3H further included 0.05 wt% alkyl diphenyl oxide disulfonate surfactant (DOWFAX® C10L). The amounts of additives are listed in Table 3.

[0050] Six separate glass disks (substrates) were polished with each composition using a Hamai 9B double-sided polishing tool under the polishing conditions previously described in Example 1. The polishing rate and surface waviness HMS_Wq were also determined as previously described in Example 1. The removal rate and surface waviness results are shown in Table 3. These results are normalized to the removal rate and surface waviness achieved using Polishing Composition 1A as reported in Table 1. TIFF2025510186000004.tif149170

[0051] As shown in Table 2, the synergistic effect previously observed in Examples 1 and 2 was observed only for compositions containing pyrophosphate compounds (compare compositions 1G and 2E, previously described in Example 2). No synergistic effect was observed for compositions containing other phosphonate and carboxylic acid additives. By adding a disulfonate anionic surfactant to a composition containing HEDP (compare 3A and 3B), a reduction in removal rate and waviness was observed (removal rate reduced to a normalized value of 136 to 116, while waviness reduced to a normalized value of 108 to 95). By adding a disulfonate anionic surfactant to a composition containing DTPMPA (compare 3C and 3D), a reduction in removal rate and waviness was observed (removal rate reduced to a normalized value of 151 to 128, while waviness reduced to a normalized value of 107 to 101). By adding a disulfonate anionic surfactant to the composition containing PBTC (compare 3E and 3F), a decrease in removal rate and waviness was observed (removal rate decreased from 181 to 114 normalized value, while waviness decreased from 132 to 95 normalized value). By adding a disulfonate anionic surfactant to the composition containing tartaric acid (compare 3G and 3H), a decrease in removal rate and waviness was observed (removal rate decreased from 138 to 129 normalized value, while waviness decreased from 116 to 100 normalized value).

[0052] Example 4 This example shows that the synergistic effect was also observed for polishing compositions using other sulfonated surfactants (in addition to DOWFAX® C10L used in Examples 1 and 2). As described above for Example 1, each polishing composition contained 8.5 wt. % colloidal silica with an average particle size of 30 nm and sufficient nitric acid to adjust the pH to 1.8. Polishing Compositions 1F, 1G, 1I, and 2E were as described above for Examples 1 and 2. Polishing Compositions 4A-4D and 4F further contained 0.12 wt. % TKPP, while Composition 4E further contained 0.08 wt. % TKPP. Polishing Compositions 4A-4F further contained 0.05 wt.% of dodecylbenzenesulfonate (DDBS) (4A), DOWFAX® C6L (4B), DOWFAX® 3B2 (4C), DOWFAX® 2A1 (4D), polyvinylsulfonic acid (PVSA) (4E), and DEQUEST® P9200 (a modified polyacrylic acid) (4F). The amounts of these additives are listed in Table 4.

[0053] Six separate glass disks (substrates) were polished with each composition using a Hamai 9B double-sided polishing tool under the polishing conditions previously described in Example 1. The polishing rate and surface waviness HMS_Wq were also determined as previously described in Example 1. The removal rate and surface waviness results are reported in Table 4. These results are normalized to the removal rate and surface waviness achieved using Polishing Composition 1A as reported in Table 1. TIFF2025510186000005.tif149170

[0054] As shown in Table 4, the synergistic effect previously observed in Examples 1 and 2 was also observed in the polishing compositions containing other sulfonate compounds. In Examples 4B, 4C, and 4D, the use of other disulfonate anionic surfactants in compositions containing TKPP was observed to increase the removal rate from a normalized value of 152 to a normalized value of 178, 179, and 155, while simultaneously decreasing the surface waviness from a normalized value of 120 to a normalized value of 109, 110, and 115. In Examples 4A and 4E, the addition of DDBS and PVSA to compositions containing TKPP was also observed to improve the removal rate and waviness. In Example 4A, the removal rate remained about the same (normalized values ​​of 153 and 152) and the waviness decreased from a normalized value of 120 to 105, while in Example 4E, the removal rate improved from a normalized value of 138 to 144 and the waviness decreased from a normalized value of 115 to 110. A combination of a non-sulfonate compound (DEQUEST® P9200) with TKPP was observed to reduce the waviness from a normalized value of 120 to 108 at the expense of a reduction in the removal rate from a normalized value of 152 to 120 (4F).

[0055] Example 5 This example shows the synergistic combination of a pyrophosphate compound and a quaternary amine compound in the disclosed polishing composition. Each polishing composition contains 8.5 wt. % colloidal silica, with an average particle size of 30 nm, and sufficient nitric acid to adjust the pH to 1.8 (except for compositions 5H and 5I, which contain sufficient nitric acid to adjust the pH to 2.3 and 2.8). Polishing compositions 1A and 1G are as described above in Example 1. Compositions 5B-5I further contain TKPP, while compositions 5A-5I further contain tetraethylammonium hydroxide in the amounts listed in Table 5 (all amounts are weight percent).

[0056] Six separate glass disks (substrates) were polished with each composition using a Hamai 9B double-sided polishing tool under the polishing conditions previously described in Example 1. The polishing rate and surface waviness HMS_Wq were also determined as previously described in Example 1. The removal rate and surface waviness results are reported in Table 5. These results are normalized to the removal rate and surface waviness achieved using Polishing Composition 1A as reported in Table 1. TIFF2025510186000006.tif155170

[0057] As shown in Table 5, by adding a quaternary amine compound (5A) (in the absence of TKPP), it was observed that the surface waviness was improved at the expense of a decrease in removal rate (removal rate was decreased to a normalized value of 82, while surface waviness was decreased to a normalized value of 88). As previously described in Example 1, by adding pyrophosphate (1G), it was observed that the removal rate was increased at the expense of an increase in surface waviness (removal rate was increased to a normalized value of 152, while waviness was also increased to a normalized value of 120). An unexpected synergistic interaction was observed for compositions 5B, 5C, 5D, 5E, 5F and 5G, in which the removal rate was significantly improved by adding a quaternary amine (TEAH in this example) to the polishing composition containing a pyrophosphate compound. Compared to composition 1G, these compositions increased the removal rate to normalized values ​​of 168, 206, 211, 207, 205, and 207. It is particularly noteworthy that compositions 5F and 5G, which contained small amounts of TKPP (0.06 and 0.03 wt%), showed significantly higher normalized removal rates of 205 and 207 (compared to compositions 1D and 1F in Example 1, which contained 0.02 and 0.08 wt% TKPP). Compositions 5H and 5I show that increasing the pH to 2.3 and 2.8 reduces the surface waviness (normalized values ​​of 132 and 125) without significantly decreasing the removal rate (normalized removal rates of 207 and 190).

[0058] Example 6 This example shows that the above-mentioned synergistic effect was observed with other quaternary amines (in addition to TEAH) in the polishing compositions. As described above for Example 5, each polishing composition contains 8.5 wt. % colloidal silica, with an average particle size of 30 nm, and sufficient nitric acid to adjust the pH to 1.8. Polishing compositions 1E and 1G are as described above for Example 1. Compositions 6A, 6B, and 6C further contain TKPP in the amounts listed in Table 6 (all amounts in weight percent). Compositions 6A and 6B contained alternative quaternary amines in the amounts listed (benzyltributylammonium chloride and tetrabutylammonium hydroxide). Composition 6C contained epsilon polylysine (a non-quaternary amine cationic compound).

[0059] Six glass disks (substrates) were polished with a Hamai 9B double-sided polishing tool under the polishing conditions previously described in Example 1. The polishing rate and surface waviness HMS_Wq were also determined as previously described in Example 1. The removal rate and surface waviness results are reported in Table 6. These results are normalized to the removal rate and surface waviness achieved using Polishing Composition 1A as reported in Table 1. TIFF2025510186000007.tif84170

[0060] As shown in Table 6, the synergistic effect previously observed in Example 5 is observed for other quaternary amines (in addition to TEAH). Compositions 6A and 6B achieved significantly higher removal rates (normalized values ​​of 186 and 185) compared to composition 1G (as did compositions 5B and 5C in Example 5). For composition 5C (a non-quaternary ammonium compound), no synergistic effect was observed, with a lower removal rate (normalized values ​​of 105:130) than composition 1E, and similar surface waviness was observed.

[0061] It is understood that recitation of a range of values ​​is intended to serve merely as a shorthand way of referring individually to each separate value falling within the range, unless otherwise indicated herein, and that each separate value is incorporated into the specification as if each value were referred to herein. All methods described herein may be performed in any suitable order, unless otherwise indicated herein or otherwise clearly contradicted by context. Any and all examples or exemplary language (e.g., "such as") used herein are intended merely to better illustrate the invention, and do not limit the scope of the claims, unless otherwise stated in the claims. No language in the specification should be construed as indicating any non-claimed element as essential to the practice of the invention.

[0062] Preferred embodiments of the present invention are disclosed herein, including the best mode known to the inventors for carrying out the invention. Variations of these preferred embodiments may become apparent to those of skill in the art upon reading the foregoing description. The inventors anticipate that such variations will be employed by those of skill in the art as appropriate, and the inventors intend for the invention to be practiced otherwise than as specified herein. Accordingly, this invention includes all modifications and equivalents of the subject matter recited in the claims appended hereto as permitted by applicable law. Moreover, any combination of the above-described elements in all possible variations of the invention is encompassed by the present invention unless otherwise indicated herein or clearly contradicted by context.

Claims

1. 1. A chemical mechanical polishing composition comprising: Liquid carrier, abrasive particles in a liquid carrier; Pyrophosphate compounds, and Sulfonate compounds, including sulfonate anionic surfactants, or anionic polymers containing sulfonic acid groups 1. A chemical mechanical polishing composition comprising:

2. The composition of claim 1 , wherein the abrasive particles comprise colloidal silica particles.

3. The composition of claim 1 , wherein the abrasive particles have an average particle size ranging from about 15 nm to about 40 nm.

4. The composition of claim 1, wherein when used, the composition contains from about 5% to about 15% by weight of abrasive particles.

5. 2. The composition of claim 1, wherein the pyrophosphate compound comprises tetrapotassium pyrophosphate (TKPP) or tetrasodium pyrophosphate (TSPP).

6. When used, from about 0.01% to about 0.2% by weight of a pyrophosphate compound; and When used, about 0.01% to about 0.2% by weight of a sulfonate compound; The composition of claim 1 comprising:

7. The composition of claim 6 , wherein the sulfonate compound comprises a disulfonate anionic surfactant.

8. The composition of claim 7, wherein the sulfonate compound comprises an alkyldiphenyloxide disulfonate anionic surfactant.

9. The composition of claim 1, wherein the pH is in the range of about 1.5 to about 3.

10. The composition of claim 1 further comprising an anionic polymer.

11. The composition of claim 10, wherein the anionic polymer is a polyacrylate polymer or a polymethacrylate polymer.

12. 1. A chemical mechanical polishing composition comprising: Liquid carrier, abrasive particles in a liquid carrier; Pyrophosphate compounds, Compounds containing a quaternary ammonium group 1. A chemical mechanical polishing composition comprising:

13. When used, from about 0.01% to about 0.2% by weight of a pyrophosphate compound; and When used, about 0.01% to about 0.2% by weight of a compound containing a quaternary ammonium group; The composition of claim 12 comprising

14. The composition of claim 12 , wherein the abrasive particles comprise colloidal silica particles.

15. The composition of claim 14, wherein the abrasive particles have an average particle size ranging from about 15 nm to about 40 nm.

16. The composition of claim 14, wherein when used, the composition contains from about 5% to about 15% by weight of abrasive particles.

17. 13. The composition of claim 12, wherein the pyrophosphate compound comprises tetrapotassium pyrophosphate (TKPP) or tetrasodium pyrophosphate (TSPP).

18. 13. The composition of claim 12, wherein the compound comprising a quaternary ammonium group comprises a tetramethylammonium group, a tetraethylammonium group, a tetrabutylammonium group, a benzyltributylammonium group, or a mixture thereof.

19. 20. The composition of claim 18, wherein the compound containing a quaternary ammonium group is tetraethylammonium hydroxide.

20. The composition of claim 12, wherein the pH is in the range of about 1.5 to about 3.

21. 1. A method for polishing a glass substrate, comprising: (a) contacting a glass substrate with the polishing composition of claim 12; (b) moving a polishing composition and a polishing pad relative to the substrate; and (c) polishing the substrate to remove a portion of the substrate to polish the surface of the substrate; A method comprising:

Citation Information

Patent Citations

  • Polishing composition for aluminum

    JP1998158634A

  • Acid for copper-based metal polishing solution, polishing solution for copper-based metals using the same, and polishing method

    JP2004006810A

  • Methods and compositions for removing residual material during substrate planarization

    JP2004526296A

  • Polishing composition and polishing method

    JP2005138197A

  • Polishing composition

    JP2006193695A